Long-term stability of guided wave electromagnetic acoustic transducer systems. (January 2020) - Herdovics, Balint; Cegla, Frederic
This article evaluates the long-term stability of a Lorentz force guided wave electromagnetic acoustic transducer. The specific application of the investigated electromagnetic acoustic transducer is pipeline health monitoring using low-frequency (27 kHz) long-range torsional guided waves. There is a concern that repeated swings in the temperature of the structure can cause irreversible changes in the transduction mechanism and therefore pose a risk to the long-term stability of transducers. In this article we report on guided wave signals acquired on a custom-built transducer while it was exposed to more than 90 heating cycles. The highest temperature that was reached during cycling was 80°C and the measurements were acquired over a 14-month period. At the end of the 1-year period, the transducer phase had changed by 23.32° and its amplitude by 3.7%. However, this change was not gradual and most of the change occurred early on, before the highest temperature was first reached in the temperature cycling process. The observed change after this was 6.08° phase shift and 0.9% amplitude change. The possible sources of output changes were investigated, and it was found that the mechanical properties of the contact layer between the electromagnetic acoustic transducer and the pipe surface was very important. A soft silicone interlayer performed best and was able to reduce temperature-induced phase changes in the monitored signals from a maximum of 80 degrees phase change to about 20 degrees phase change, a fourfold reduction.